Long Distance Love - Gertten, Magnus; Jönsson, Elin (Auto Images, 2009)
Verzio FF Shortly after the honeymoon of 18-year-old Alisher and his 17-year-old wife Dildora is over, Dildora gets pregnant. But how is Alisher going to take care of his wife and the baby, being unemployed in Kyrgyzstan? Like many inhabitants of the Kyrgyz Republic Alisher decides to try to make it big in Moscow. One out of four men in Kirgizia leaves the country — mostly for Russia. The migrant workers often have a hard time. The twelve to sixteen million foreign workers in Russia get the worst paid jobs and live squeezed together in small apartments. To make things worse, Alisher is cheated by the agency which acts as an intermediary between him and his Russian employers. Meanwhile, his family is desperately waiting for the money from Moscow to arrive. Will the love between Alisher and Dildora last, now that 2,500 miles separate them? A film about love, hope, migration and the daily struggle for survival in a part of the world rarely explored.